Автоматизированный анализ и оценка результатов тестирования производительности высоконагруженных систем - Деряка, Е. В. (ХНУРЕ, 2019)
The proposed work is devoted to finding and analyzing existing algorithms or developing a custom algorithm for automatically analyzing the results of performance testing of high-loaded systems based on previously obtained data and system configuration. The developed algorithm will be useful for performance analysts to reduce the time spent on obtaining test results. In the course of work, the algorithm should be able to provide the main points of results (as saturation point and failure point) and predict the possible behavior of the system in the future depending on the configuration change.